2019
DOI: 10.1128/jvi.00199-19
|View full text |Cite
|
Sign up to set email alerts
|

Cell Entry-Independent Role for the Reovirus μ1 Protein in Regulating Necroptosis and the Accumulation of Viral Gene Products

Abstract: The reovirus outer capsid protein 1 regulates cell death in infected cells. To distinguish between the roles of incoming, capsid-associated, and newly synthesized 1, we used small interfering RNA (siRNA)-mediated knockdown. Loss of newly synthesized 1 protein does not affect apoptotic cell death in HeLa cells but enhances necroptosis in L929 cells. Knockdown of 1 also affects aspects of viral replication. We found that, while 1 knockdown results in diminished release of infectious viral progeny from infected c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 55 publications
(83 reference statements)
1
20
0
Order By: Relevance
“…The levels of outer capsid protein µ1 modulate cell death (10). Our work indicates that newly synthesized µ1 negatively regulates the induction of necroptosis in L929 cells by preventing excessive accumulation of viral gene products.…”
Section: Knockdown Of Newly Synthesized σ3 Drives An Increase In Cellmentioning
confidence: 80%
See 2 more Smart Citations
“…The levels of outer capsid protein µ1 modulate cell death (10). Our work indicates that newly synthesized µ1 negatively regulates the induction of necroptosis in L929 cells by preventing excessive accumulation of viral gene products.…”
Section: Knockdown Of Newly Synthesized σ3 Drives An Increase In Cellmentioning
confidence: 80%
“…These data suggest that newly synthesized σ3 negatively regulates cell death in L929 cells following reovirus infection. L929 cells infected with reovirus undergo RIP3-dependent necroptosis (9,10). It is possible, however, that σ3 knockdown changes the nature of cell death in these cells.…”
Section: Knockdown Of Newly Synthesized σ3 Drives An Increase In Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…replication and cell death demonstrated that this outer capsid protein limits the cell death response by negatively regulating viral replication events (10). We observed that knockdown of newly synthesized µ1 results in increased production of secondary transcripts and dsRNA genome.…”
Section: Loss Of σ3 Does Not Impact Replication Events Our Recent Womentioning
confidence: 81%
“…Many cell lines, including L929, Hela, LLC‐MK2 and MDCK cells, are susceptible to MRV infection and used for virus isolation (Desrosiers & Lengyel, 1979; Ooms, Kobayashi, Dermody, & Chappell, 2010; Roebke & Danthi, 2019; Rozee & Easterbrook, 1970). However, the general ubiquity of infectious microbes in swine faecal specimens has made the virus isolation difficult.…”
Section: Introductionmentioning
confidence: 99%